RICE STRAW FOR INTERIOR ELEMENTS OF A LOCAL “WEDANGAN” CULINARY BUSINESS IN SURAKARTA - Sumarno Sumarno; Dharsono Dharsono; N.R. Ardi Candra Dwi Atmaja (ARTISTIC : International Journal of Creation and Innovation, 2021)
Rice straw is abundant and inexpensive as post-harvest crop residue. Rice straw can be processed into a variety of products for interior space filling through creative efforts. This research seeks to empower farmers by utilizing rice straw as crop residue and to create natural-style products for the interior space-filling of a local culinary business (wedangan), as wedangan is a typical culinary business that is traditional, fast-growing, and trendy in Surakarta City and its surroundings. The design method is based on design thinking procedures, which include empathizing, defining, ideating, prototyping, and testing. Empathy for low-income farmers is expected to add value and profit through rice straw processing. Wedangan's interior space-filling products are designed around the kantong semar flower (Nepenthes sp.). The prototype (as a design embodiment) is developed in collaboration with the farmers. This type of experience is intended to serve as training and assistance. Product testing is conducted through market research and product application in  wedangan interiors in this city. As a result, business managers and visitors alike appreciate interior space-filling products. Economically, this product development for interior space filling represents a viable business opportunity for farmers to pursue as a secondary occupation.